EVALUASI PERTUMBUHAN RUMPUT LAUT (EUCHEUMA COTTONII) PADA BUDIDAYA METODE LONG LINE DI PERAIRAN PANTAIKABUPATEN BANGGAI KEPULAUAN - Tasruddin Tasruddin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2015)
Seaweed (Eucheuma cottonii) is one type of fishery commodities with high economic value. These commodities have been developed in several areas in Indonesia, one of them is in the Banggai Islands, Central Sulawesi. Problems in the development of commodity seaweed in Banggai is a lack of understanding and seriousness in seaweed cultivation, lack of variety in designing seaweed cultivation techniques as well as the suitability of the location of aquaculture that can support increased productivity. The use of long-line method is considered still the best way. This study aimed to evaluate the seaweed cultivation methods long line in the village of Liang and Apal, Banggai Islands, Central Sulawesi. The results showed that the seaweed growth rate were not significantly different when we compared them based on sediment types. For instance, Liang village sediment was sandy silt while we found rocky substrate at Apal village. Therefore it can be concluded that long line method can be applied without taking into account the type of sediment. Keywords: sea weed, long-line methods, Banggai archipelago